Dysfunctions of the immune system associated with age - Patrycja Wszelaki; Michał Wilczyński; Beniamin Piotr Szmelcer; Aleksander Florczak; Aleksandra Fortuna; Daria Zaborna; Natalia Krakowska; Agata Trzebiatowska; Justyna Ciepłuch; Natalia Skierkowska; Mateusz Porada; Mariusz Wąsicki; et al. (Kazimierz Wielki University, 2019)
Abstract Background: The human immune system consists of innate and adaptive responses. Innate immune response is the first line of the body's defense, while the adaptive response eliminates pathogens in later stages of infection. Cooperation between innate and adaptive immune response is important to effectively eliminate pathogens. An integral part of the aging of the human body is the aging of the immune system, which results in functional disorders directly affecting the deterioration of health. Abnormal functioning of the immune system is a predisposing factor to the occurrence of old-age diseases, as well as reduces the effectiveness of protective vaccination especially recommended to geriatric patients. Material and Methods: The current state of knowledge on age-related immune dysfunctions has been reviewed. The analysis concerned publications in English and Polish language published in the years 2003-2018, which were collected in the PubMed and Google Scholar database. Particular attention was paid to publications presenting the results of research conducted on a group of geriatric people in order to analyze the facts from the research. The publications were searched on the basis of key phrases, among others: the immune system of the elderly, chronic inflammation, innate immunity and adaptive immunity. Results: A review of current knowledge showed the seriousness of the problem of the aging of the immune system. In addition to reducing the efficiency of the immune system, special attention should be paid to chronic inflammation that predisposes to old-age diseases, as well as to reduce the effectiveness of immunization, which is a serious threat. Conclusion: Analyzing the sources of chronic inflammation in the elderly, particular attention was paid to the phenotype of aging cells, changes in the intestinal microflora of the elderly, the role of adipose tissue in the process of inflammation and changes in the levels of steroid hormones. Public awareness of the etiology of the problem is an excellent method of counteracting the negative effects of immunodeficiency. One of the recommendations is physical activity as part of the elimination of adipose tissue capable of securing an infinite number of pro-inflammatory cytokines.